Contemporary police stress: the impact of the evolving socio-political context - J. Saunders; V. Kotzias; R. Ramchand (Russian Journal of Economics and Law, 2019)
Objective: to study stress in the work of law enforcement agencies under the changing socio-political environment. Methods: dialectic approach to the cognition of social phenomena, allowing to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, sociological.Results: interviews with representatives from 110 law enforcement agencies showed how occupational stressors have changed in recent years. The most frequently cited stressors involved day-to-day enforcement activities that put officers in potentially dangerous situations, the administrative burden and shift work associated with the profession, family and relationship challenges that accompany the job, and the state of police community relations and negative portrayal of the police by the media. Respondents reported that officers experience increased fear and stress due to recent changes in the socio-political environment, which is characterized by strained police-community relations, increased scrutiny associated with the 24-hr news cycle, and the ubiquity of personal recording devices and sharing videos on social media.Scientific novelty: for the first time, the work presents an analysis of the impact of stress in the law enforcement agencies under the changing socio-political environment. The new positive factors which have changed the landscape of police stress for the better are: 1) the current socio-political environment; 2) generational shifts in the workforce and; 3) efforts to destigmatize mental health care.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activity when viewing and studying the issues related to stress in the work of police officers under the changing socio-political environment.